Diplodia sapinea: the main fungal species involved in the colonization of pine shoots in Italy. Issue 5 (31st March 2014) - Luchi, N.; Oliveira Longa, C. M.; Danti, R.; Capretti, P.; Maresi, G.; Roux, J.
Summary Damage to various forest tree species caused by Diplodia sapinea has been reported in Italy since the early 20th century. However, until recently, systematic characterization of this microorganism, based on DNA sequence data, has been limited with only a general description of the fungus in the majority of the reports. To address this and provide a more accurate identification of Diplodia species associated on pine in Italy, we examined a total of 88 Botryosphaeriaceae isolates obtained from symptomatic and asymptomatic material from different hosts located in different geographical regions of Italy. Using molecular analysis, we were able to identify 67 isolates of D. sapinea and eight isolates of D. seriata. Diplodia sapinea was dominant on P. nigra shoots and was also detected on P. halepensis, P. pinea, P. pinaster, P. radiata and P. sylvestris, while D. seriata and other Botryosphaeriaceae appeared to be only occasionally present on shoots. The remaining 13 isolates represented nine different Botryosphaeriaceae species, occurring at low levels. Analysis of molecular variance (amova) based on DAMD‐PCR profiles detected low significant differences among D. sapinea isolates from the different sampling areas throughout Italy.